Fabricating high performance conventional and inverted polymer solar cells by spray coating in air. (May 2017) - Zhang, Yiwei; Scarratt, Nicholas W.; Wang, Tao; Lidzey, David G.
Abstract: We report bulk heterojunction organic solar cells utilising the electron-donating polymer PffBT4T-2OD blended with the fullerene acceptor PC71 BM, with cells explored based on both conventional and inverted architectures. As charge-transporting layers, we utilise the hole-transporting polymer poly (2, 3-dihydrothieno-1, 4-dioxin)-poly (styrenesulfonate)( PEDOT:PSS) in conventional device architectures, and zinc oxide (ZnO) electron-transport in inverted devices. Critically, all charge-transporting layers and the poly[(5, 6-difluoro-2, 1, 3-benzothiadiazol-4, 7-diyl)-alt- (3, 3‴-di(2-octyldodecyl) 2, 2'; 5′, 2''; 5″, 2‴ -quaterthiophen-5, 5‴-diyl)] (PffBT4T-2OD): [6, 6]-phenyl C71 butyric acid methyl ester (PC71 BM) active layer blend were spray coated in air. We demonstrate champion devices having a power conversion efficiency of 8.13% and 8.43% for conventional and inverted architectures respectively. Highlights: PEDOT:PSS, ZnO precursor and PffBT4T-2OD:PC71 BM films were fabricated via spray coating in air. The PCE of OPV devices utilising a PEDOT:PSS hole transport layer and PffBT4T-2OD:PC71 BM active-layer was 8.13%. The PCE of OPV devices utilising the ZnO electron transport layer and PffBT4T-2OD:PC71 BM active-layer was 8.43%.